Are we missing the target?: cancer stem cells and drug resistance in non-small cell lung cancer - Gottschling, Sandra; Schnabel, Philipp Albert; Herth, Felix; Herpel, Esther (Cancer genomics & proteomics, 2012)
Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related death in Western countries. Despite novel molecular therapies, the majority of patients with advanced or metastatic disease show rapid progression and a median survival time of not more than 18 months. In the last decade, there has been increasing evidence that cancer stem cells (CSC) play a pivotal role in drug resistance, tumour regeneration and metastasis of various cancer entities including lung cancer. In this review, we discuss the evidence for stem cells in NSCLC, their predictive and prognostic significance, their specific mechanisms of resistance and potential targets and strategies for eradication of these cells. Consideration of the specific properties of CSC in lung cancer therapy might substantially contribute to increased response and prolonged survival rates in this disease.